Pengaruh Citra Merek, Promosi, Kualitas Pelayan Dan Store Atmosphere Terhadap Kepuasan Konsumen - Nasrul Efendi; Tya Wildana Hapsari Lubis; Sugianta Ovinus Ginting (Jurnal Ekonomi, 2023)
This study aims to determine the partial and simultaneous effects of brand image, promotion, service quality and store atmosphere on customer satisfaction. This type of research is associative research, namely research that aims to find out some cancellations regarding whether or not there is a relevant relationship between two or more research variables. The sampling technique uses a non-probability sampling technique with an accidental sampling approach with a sample size of 167 respondents. Based on research data processing, it is known that brand image, service quality and store atmosphere partially affect consumer satisfaction. While promotions partially have no effect on consumer satisfaction. Then, the results of the study simultaneously show that brand image, promotion, service quality and store atmosphere affect consumer satisfaction with a determination value (R²) of 0.628 which means that brand image, promotion, service quality and store atmosphere are able to explain consumer satisfaction of 62.800 percent.